The Entrepreneur's Cognitive and Behavioral Journey: Understanding Heuristics and Bias under Risk and Uncertainty - Veronica Cucchiarini; Sergio Scicchitano; Riccardo Viale (Global Labor Organization (GLO), 2024)
The study of the entrepreneurial mindset has provided valuable insights into the cognitive strategies that impact entrepreneurial activities. Researchers have identified several biases and heuristics employed by entrepreneurs, which significantly influence their decision-making processes and actions, but the empirical evidence remains fragmented. To develop a more comprehensive understanding of the cognitive and behavioral mindset of entrepreneurs, it is important to consider the role of the context in which they operate. By analyzing the strengths and weaknesses of heuristics and biases within the context of risk or uncertainty, we can gain a deeper understanding of their influence on entrepreneurial outcomes.
Keywords: 330; Entrepreneurship; biases; heuristics; risk; uncertainty; labour policies